Kinematic alignment in robotic total knee arthroplasty - Alexey V. Lychagin; Andrey A. Gritsyuk; Eugene B. Kalinsky; Yaroslav A. Rukin; Mikhail P. Elizarov; Andrey А. Gritsyuk; Maxim Ya. Gavlovsky; Konstantin Kh. Tomboidi; Milana L. Babaeva (Гений oртопедии)
Introduction There are two main concepts of total knee arthroplasty: mechanical and anatomical alignment of the lower limb axis. Howell et al. (2013) proposed the concept of kinematic alignment, the main idea of which is to preserve the level of the joint line and the axis of the lower limb that patients had before the onset of osteoarthritis. Initially, kinematic alignment was proposed to be performed with individual guides based on the results of CT/MRI scans but they took a long time to manufacture, were difficult to install, broke down, and were quite expensive. Introduction of robotic orthopaedic systems into clinical practice enabled to plan and perform bone resection with high accuracy, to install the components of the implant system according to the necessary concept thus providing new opportunities for the application of kinematic alignment, which was the purpose of our study. Purpose To study the possibilities of a robotic surgical system in performing restricted kinematic alignment in total knee arthroplasty (TKA). Materials and methods A prospective single-center study was conducted in 47 patients (12 men and 35 women) with knee osteoarthritis in Kellgren – Lawrence grades 3–4, an average age of (65.87 ± 7.4) years, an average BMI of (31.3 ± 4.7) kd/m2, median HKA angle of 175°, median LDFA of 87°, median MPTA of 87°. The patients underwent robotic total knee arthroplasty (RoTKA) with the method of restricted kinematic alignment. Results On the control whole-leg radiographs, the average HKA angle after surgery was (176 ± 1.5)°. In 42.6 % of cases, the deviation from the plan was within ± 1°, the deviation ± 2° in 44.7 % of cases, and in the remaining 12.7 % of cases the deviation was negative. Discussion In the literature, we did not find the results of radiographic evaluation of the HKA angle in the coronal view before and after robotic total knee arthroplasty and their comparison with the results of preoperative planning using the kinematic alignment method of the limb axis. The results we obtained show high accuracy of the implementation of the preoperative plan. Conclusion A personalized approach to TKA with application of an autonomous robotic system effectively provides kinematic alignment of the axis of the lower limb with an accuracy of up to 2° in 87.3 % of patients.